2010
DOI: 10.1152/ajpcell.00100.2009
|View full text |Cite
|
Sign up to set email alerts
|

The P2Y2 receptor mediates the epithelial injury response and cell migration

Abstract: Injury to epithelial cells results in the release of ATP and stimulation of purinergic receptors and is thought to alter cell migration and wound repair. Medium from the injured cells triggers Ca(2+) mobilization and phosphorylation of ERK, both of which are inhibited if the medium is pretreated with apyrase. To understand the wound repair mechanism that occurs with injury, our goal was to determine which purinergic receptor(s) was the critical player in the wound response. We hypothesize that the P2Y(2) recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 38 publications
3
81
1
Order By: Relevance
“…However, unlike other purinoreceptors, such as P2Y2, we found that P2X7 does not influence the distance or rate of Ca 2þ wave propagation from the site of injury. 3,4 Because the region of cells in which P2X7 modulates calcium dynamics correlates with the region of wounded epithelium in which P2X7 expression increases after injury, we speculate that localized activation of P2X7 acts in a feed-forward manner to up-regulate its expression at the leading edge.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, unlike other purinoreceptors, such as P2Y2, we found that P2X7 does not influence the distance or rate of Ca 2þ wave propagation from the site of injury. 3,4 Because the region of cells in which P2X7 modulates calcium dynamics correlates with the region of wounded epithelium in which P2X7 expression increases after injury, we speculate that localized activation of P2X7 acts in a feed-forward manner to up-regulate its expression at the leading edge.…”
Section: Discussionmentioning
confidence: 90%
“…To further determine specificity, cells were also stimulated with either UTP or ADP, agonists for P2Y2 and P2Y4 or P2Y1, respectively, three other G-proteinecoupled purinoreceptors that are expressed in HCLE cells. 4,18 Treatment with oxATP, A438079, or siRNA to P2X7 did not significantly inhibit the UTP-or ADP-stimulated Ca 2þ response (Figure 3, C and D).…”
Section: Role Of P2x7 In Calcium Mobilizationmentioning
confidence: 92%
See 3 more Smart Citations